Hybrid languages, translation and post-colonial challenges - Price, Joshua M.; Pulido (Traductora), Martha; Guzmán (Traductora), María Constanza (Íkala, Revista de Lenguaje y Cultura, 2007)
Multilinguality, creolization and hybridisation are central phenomena of language. Languages bear the traces of creative borrowing, as well as forced changes as a consequence of domination. However, mainstream translation theory generally seems to presuppose a clear division between source language and target language. Why the persistence not to see the ways languages intermesh? In this essay I 1) argue the importance of multilinguality for translation theory, 2) suggest that the theoretical insistence in not seeing the way languages intermesh is grounded in an Occidentalist preoccupation with I/Other relations which require strict dichotomization and 3) disrupt the dichotomy with insurgent texts and voices which countermand the tendency to erase any kind of linguistic mixing. I conclude by proposing a methodology for taking fuller stock of the play of power and the plurality. Received: 08-04-07 / Accepted: 06-08-07 How to reference this article: Price, J. M. (2007). Lenguas híbridas, traducción y desafíos poscoloniales. Íkala. 12(1), pp. 61 – 93.